14-Electron Rh and Ir silylphosphine complexes and their catalytic activity in alkene functionalization with hydrosilanes. Issue 34 (9th August 2021) - Abeynayake, Niroshani S.; Zamora-Moreno, Julio; Gorla, Saidulu; Donnadieu, Bruno; Muñoz-Hernández, Miguel A.; Montiel-Palma, Virginia
Abstract : 14-electron Rh and Ir species as robust catalysts for silicon functionalization. Abstract : Herein we report an experimental and computational study of a family of four coordinated 14-electron complexes of Rh(iii ) devoid of agostic interactions. The complexes [X–Rh(κ 3 ( P, Si, Si )PhP( o -C6 H4 CH2 Si i Pr2 )2 ], where X = Cl (Rh-1 ), Br (Rh-2 ), I (Rh-3 ), OTf (Rh-4 ), Cl·GaCl3 (Rh-5 ); derive from a bis(silyl)- o -tolylphosphine with isopropyl substituents on the Si atoms. All five complexes display a sawhorse geometry around Rh and exhibit similar spectroscopic and structural properties. The catalytic activity of these complexes and [Cl–Ir(κ 3 ( P, Si, Si )PhP( o -C6 H4 CH2 Si i Pr2 )2 ], Ir-1, in styrene and aliphatic alkene functionalizations with hydrosilanes is disclosed. We show that Rh-1 catalyzes effectively the dehydrogenative silylation of styrene with Et3 SiH in toluene while it leads to hydrosilylation products in acetonitrile. Rh-1 is an excellent catalyst in the sequential isomerization/hydrosilylation of terminal and remote aliphatic alkenes with Et3 SiH including hexene isomers, leading efficiently and selectively to the terminal anti-Markonikov hydrosilylation product in all cases. With aliphatic alkenes, no hydrogenation products are observed. Conversely, catalysis of the same hexene isomers by Ir-1 renders allyl silanes, the tandem isomerization/dehydrogenative silylation products. A mechanistic proposal is made to explain the catalysis with these M(iii ) complexes.